Relationship between Knowledge and Readiness to Face Menopause in Perimenopausal Women in Sumberrejo Village: Relationship between Knowledge and Readiness to Face Menopause in Perimenopausal Women in Sumberrejo Village - Raudatul Hikmah; Dwi Margareta Andini; Dewi Andariya Ningsih (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Menopause is a phase in which women experience the cessation of menstrual cycles during the climacteric period. At around 45 years of age, there is a decrease in ovarian function which causes the production of the hormone estrogen to decrease. According to (WHO) for 2025, the number of women experiencing menopause in the Asian region is expected to increase significantly, from 107 million to 373 million. Meanwhile, (Ministry of Health of the Republic of Indonesia) estimates that in 2020, the population of Indonesia will reach around 262.6 million, with around 30.3 million women in the menopause phase. Their average age when experiencing menopause is 49 years. Objectives: To determine the relationship between knowledge and readiness to face menopause in perimenopausal women in Sumberrejo Village, Banyuputih District. Methods: This study is a quantitative analytical study with a cross-sectional research design. The population of the study was all perimenopausal women in Sumberrejo Village, Banyuputih District, totaling 641 people. The sampling technique was Purposive Sampling with a sample size of 89 people. Results: Based on the results of the knowledge analysis, 33 respondents (37.1%) had good knowledge, 41 respondents (46.1%) had sufficient knowledge and 15 respondents (16.9%) had insufficient knowledge. The results of the analysis of respondent readiness were in the category of being ready to face menopause with 76 respondents (85.4%) and 13 respondents (14.6%) were not ready to face menopause. The Kolmogorov Smirnov non-parametric analysis test showed that the significance value obtained was 0.000, the significance value was <0.05 (p <0.05). Conclusions: it can be concluded that there is a relationship between knowledge and readiness to face menopause in perimenopausal women in Sumberrejo Village, Banyuputih District